Semi-dynamic pilot allocation based on graph coloring in massive MIMO systems - Fangmin XU; Hui QIAN; Haiyan CAO (Dianxin kexue)
To alleviate the performance loss caused by pilot contamination in massive multiple-input multiple-output (MIMO) systems,a semi-dynamic pilot allocation scheme based on graph coloring was proposed.Firstly,a pilot reuse threshold was derived for users.Then,based on the pilot reuse threshold,users of each cell are divided into cell-center users and cell-edge users,where cell-center users were allowed to reuse the same pilot.Finally,based on the graph coloring theory,the pilot resources were allocated to cell-edge users with serious pilot interference by multi-cell coordination.The simulation results show that the proposed pilot allocation scheme reduces the pilot interference and improves the uplink achievable rate of the whole system effectively.